PERLINDUNGAN PEREMPUAN DAN ANAK: STUDI AKIBAT HUKUM PENGABAIAN PENCATATAN PERKAWINAN - Sukiati, Sukiati; Bancin, Ratih Lusiani (Universitas Islam Negeri Ar-Raniry, 2020)
Marriage registration becomes a very important element for the validity of marriage. An unregistered marriage has a direct effect on the woman (wife) and child. This problem is one of references for the importance of registering marriage. Marriage registration aims to fulfill women and children’s rights as legal subjects. The work intends to explain how urgent the registration of marriage is in protecting women and children. Using research libraries, data are collected by exploring data sources that are relevant to the topics discussed. This study concludes that the legal impact arising from neglecting marriage registration is not easy. When a dispute occurs, the wife of an unregistered marriage cannot sue her husband. In this case, the wife's position is very weak. Likewise with children, the status of children born is considered as illegitimate children. The child’s unclear status in the eyes of the law causes the parent-child relationship is not strong, so parents may be able to deny his biological child.